2020
DOI: 10.1136/bmjresp-2020-000696
|View full text |Cite
|
Sign up to set email alerts
|

Dance for people with chronic breathlessness: a transdisciplinary approach to intervention development

Abstract: ObjectivesA transdisciplinary research approach was used to develop a holistic understanding of the physical and psychosocial benefits of dance as an intervention for people living with chronic breathlessness.MethodsThe dance programme was developed in collaboration with British Lung Foundation Breathe Easy members in NE England (Darlington) and London (Haringey). Members of the Darlington group were invited to participate in the programme. An exercise instructor, trained and mentored by a dance facilitator de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 37 publications
2
44
1
1
Order By: Relevance
“…As regards the seven studies included in this systematic review, all were published in the last 3 years [ 27 , 28 , 29 , 30 , 31 , 32 ], except one [ 33 ], which was published in 2005. Five studies investigated adults [ 27 , 28 , 29 , 30 , 31 ], whereas one study investigated children [ 32 ], and one final article investigated a population of people aged 17 years old or older [ 28 ]. All the seven studies were conducted in urban areas.…”
Section: Resultsmentioning
confidence: 99%
“…As regards the seven studies included in this systematic review, all were published in the last 3 years [ 27 , 28 , 29 , 30 , 31 , 32 ], except one [ 33 ], which was published in 2005. Five studies investigated adults [ 27 , 28 , 29 , 30 , 31 ], whereas one study investigated children [ 32 ], and one final article investigated a population of people aged 17 years old or older [ 28 ]. All the seven studies were conducted in urban areas.…”
Section: Resultsmentioning
confidence: 99%
“… 52 Resultant improvements to physical fitness include improved exercise capacity and greater strength and balance. 53 Wshah et al 54 confirmed that dance performed twice a week for 8 weeks increased the 6-min walking distance and improved the dyspnoea of patients with COPD. The enjoyment and social connections experienced in dance classes may also play an important role in improving mood and encouraging attendance and completion of the therapy.…”
Section: Discussionmentioning
confidence: 95%
“…The enjoyment and social connections experienced in dance classes may also play an important role in improving mood and encouraging attendance and completion of the therapy. 53 Therefore, dance effectively improves functional capacity, balance, emotion, anxiety and depression, physical activity and health-related quality of life of both healthy people and those with chronic respiratory disease, 52 , 53 , 55 , 56 whereas music, singing and dancing enhance participation, improve disease management and boost mood and self-confidence, 57 , 58 potentially helping to enhance confidence and reduce psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Programas como el Life Rainbow Programme (LRP) realizan intervenciones de este tipo en pacientes con enfermedades crónicas no neoplásicas, como la EPOC, reportando resultados positivos como mejora significativa de la calidad de vida y disminución la estancia hospitalaria (Law et al, 2020); por otra lado, el desarrollo de un programa de baile como medida de intervención a través de un enfoque transdisciplinar sugiere beneficios físicos y psicosociales en personas con sensación crónica de falta de aire que han de ser corroborados mediante un ensayo clínico aleatorizado (Harrison et al, 2020).…”
Section: Fuente: Elaboración Propiaunclassified